Аксіонне гало навколо подвійної системи карликових зірок - Patkós, A. (Publishing house "Academperiodika", 2024)
The gravitational field of a clump of ultralight axion like particles (ALPs) in its core with a rotating binary system of dwarf stars is computed. It is established that the induced quadrupole mass moment of the clump is controlled parametrically by the Ma/M mass ratio of the axion clump and the binary core.